2014
DOI: 10.1123/jpah.2012-0043
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Activity and Sedentary Behavior in a Randomized Trial of an Internet-Based Versus Workbook-Based Family Intervention Study

Abstract: Background The America on the Move (AOM) Family Intervention Program has been shown to prevent excess weight gain in overweight children. Providing intervention materials via the internet would have the potential to reach more families but may increase sedentary behavior. The purpose was to evaluate whether delivering the AOM Family Intervention via the internet versus printed workbook would have a similar impact on sedentary behaviors in children. Methods 131 children (age 8–12) were randomized to receive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…Social support is a well-known mediator of physical activity and weight management in AA women [33,64-66]. In the current study, social support also emerged as a potential mediator to yogic dance.…”
Section: Discussion/conclusionsupporting
confidence: 48%
“…Social support is a well-known mediator of physical activity and weight management in AA women [33,64-66]. In the current study, social support also emerged as a potential mediator to yogic dance.…”
Section: Discussion/conclusionsupporting
confidence: 48%
“…Forty‐seven interventions met inclusion criteria (Fig. ), of which 31 (66%) demonstrated a significant positive effect on physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…based delivery of PA interventions shows promise for enhancing diabetes and chronic disease self-management, more methods to sustain involvement with Internet-based PA interventions are needed . In a randomized, controlled trial of an Internet PA intervention versus printed workbooks alone, those in the printed workbook group were less likely to remain in the study and did not improve their sedentary behavior when compared to those in the Internet group (Catenacci et al, 2013).…”
Section: The Internet and Aasmentioning
confidence: 95%
“…Using the Internet to deliver PA. Several studies (Catenacci et al, 2013;Riiser, Løndal, Ommundsen, Sundar, & Helseth, 2013;) have demonstrated the use of the Internet as a resource for delivering PA interventions. An investigation of a theory-based Internet intervention using behavioral PA strategies supplemented with weekly, individualized information (tips sheets) to enhance PA uptake in sedentary adults demonstrated short-term benefits of moderateintensity PA both at 1-and 3-month follow-ups.…”
Section: The Internet and Aasmentioning
confidence: 99%
See 1 more Smart Citation